Pengaruh Stabilitas Keuangan, Ineffective Monitoring, Pergantian Auditor, Pergantian Dewan Direksi Terhadap Indikasi Kecurangan Laporan Keuangan pada Perusahaan Energi yang Terdaftar di BEI Priode 2022-2023 - Aprilia Kurnia Putri; Hairul Anam; Butet Wulan Trifina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the effect of financial stability, ineffective monitoring, change of auditors, change of directors on indications of fraudulent financial reports in energy companies listed on the Indonesia Stock Exchange. Sample selection used a purposive sampling method with a research period of 2022-2023. The samples obtained in this research were 22 samples from 88 populations. The data analysis technique used is multiple linear regression analysis using SPSS 25. The results of the research show that financial stability has an effect on indications of fraudulent financial reports. Meanwhile, ineffective monitoring, changing auditors and changing the board of directors have no effect on indications of fraudulent financial statements.